The Flouts of Grice’s Maxims in An Animated Cartoon Serial Spongebob Squarepants - Kusumo, Destra Wibowo; Mujiyanto, Januarius; Sutopo, Djoko (Universitas Negeri Semarang, 2018)
This study attempts to explain the flouts of Grice’s maxims as well as the relation between verbal and visual representations in an animated cartoon serial. The descriptive qualitative approach with the content analysis is used in the research design. The data are in the form of verbal and visual representations. The verbal data are the utterances taken from the dialogs; the visual data are the screen captures from the scenes in SpongeBob SquarePants. The results of the study show that all the four Grice’s maxims, namely quantitative, qualitative, relation and manner, are flouted. The maxims of quantity are flouted through too little and too much information. Next, the maxims of quantity are flouted through untrue information and information with lack of evidence. Next, the maxim of relation is flouted through non-relevant information. Finally, the maxim of manner is flouted through ambiguous, obscure, and lengthy information. Meanwhile, to deal with the relationship between verbal and visual elements in the flouts of maxims, the verbal or linguistic representations are evidently supported by the visual ones. The visual analysis in flout of maxims plays the essential role as it can get the pragmatic contexts clearer to help the analysis.